Sidq wa Tsabat Bunud As’ilah Ikhtibar At-Taqyim At-Tajmi' An-Niha'i Li Maddah Al-Lugah Al-Arabiyah Bi Al-Madrasah Al-Mutawasitah Malang - Mufidha, Ulfatul; Ibrahim, Fikri Haikal; Gafur, Abdul; Anshori, Muhammad Ridho; Qomari, Nur (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
This study aims to analyze the validity and reliability of the final year summative exam (SAT) questions for the Arabic language subject for class VII of SMP Integral Malang. The subjects of this study were 25 students of class VII C, while the data were in the form of students' raw scores from the multiple-choice questions that had been completed. The method used in this study was a descriptive quantitative type, with data collection in the form of documentation. Data analysis was carried out using the IBM SPSS Statistic 25 application. The results of the analysis of the final year summative exam (SAT) questions for class VII of SMP Integral Malang showed that out of 33 multiple-choice questions, only 9 questions were valid, while 24 questions did not meet the validity criteria, with reference to the calculated r value> r table and Sig. <0.05. However, the reliability value using Cronbach's Alpha was 0.657, which was greater than the r table (0.396), indicating a high level of question reliability. This finding reveals that an instrument can remain reliable even though most of the questions are invalid. The results of this study provide an empirical basis for teachers to conduct evaluations and improvements in the preparation of questions and become an academic reference in developing evaluations of Arabic language learning at the junior high school level.